1987
DOI: 10.1038/ki.1987.267
|View full text |Cite
|
Sign up to set email alerts
|

Arterial hypotension in chronic hemodialyzed patients

Abstract: We studied in 32 patients on maintenance hemodialysis (duration of treatment 6 to 133 months) whether duration of dialysis treatment affects blood pressure, plasma noradrenaline levels and alpha 2-adrenoceptor density (assessed in platelet membranes by 3H-yohimbine binding). Plasma noradrenaline levels were a significant inverse correlation to platelet alpha 2-adrenoceptor density. In addition, mean arterial blood-pressure, plasma noradrenaline levels and platelet alpha 2-adrenoceptor density were significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
39
0
2

Year Published

1990
1990
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(44 citation statements)
references
References 25 publications
3
39
0
2
Order By: Relevance
“…In conclusion: patients on maintenance hemodialysis exhibit numerous alterations in the activity of the sympathetic nervous system [1, 2, 3]including hyporesponsiveness of α- and β-adrenoceptors [4, 7, 22, 23]. The present results show that for β-adrenoceptor hyporesponsiveness – at least partly – the presence of inhibitory substance(s) in uremic plasma could be responsible; the mechanism leading to α-adrenoceptor hyporesponsiveness remains to be elucidated.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In conclusion: patients on maintenance hemodialysis exhibit numerous alterations in the activity of the sympathetic nervous system [1, 2, 3]including hyporesponsiveness of α- and β-adrenoceptors [4, 7, 22, 23]. The present results show that for β-adrenoceptor hyporesponsiveness – at least partly – the presence of inhibitory substance(s) in uremic plasma could be responsible; the mechanism leading to α-adrenoceptor hyporesponsiveness remains to be elucidated.…”
Section: Discussionmentioning
confidence: 85%
“…Thus, the β-adrenoceptor agonist isoprenaline causes smaller increases in systolic blood pressure in hemodialysis patients than in controls [4]; the heart rate response to isoprenaline is also reduced in experimental uremia in rats [5]. Similarly, vascular α-adrenoceptor responsiveness was found to be reduced in chronic hemodialysis patients [6, 7]and in experimental uremia in rats [8, 9]. The mechanism underlying this α- and β-adrenoceptor hyporesponsiveness in chronic uremia is, however, only poorly investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Our results show that hypotension during HD is closely associated with severe coronary arteriosclerosis, suggesting that reduced coronary blood flow capacity diminishes cardiac compensation for the loss of blood volume. Dual et al [28]demonstrated that the duration of HD negatively correlated with both the mean BP and α 2 -adrenoceptor density, and positively correlated with plasma noradrenaline level. Moreover, they noted that a reduction in α 2 -adrenoceptor responsiveness to α-adrenergic stimuli might be an important cause of hypotension in patients undergoing long-term HD treatment [28].…”
Section: Discussionmentioning
confidence: 99%
“…Re cently. it has been shown that the concentra tion of plasma noradrenaline increased sig nificantly with increasing duration of dialysis treatment [4]. The absence o f receptor downregulation in the presence o f a high concen tration o f the physiological agonist could he the consequence o f an altered receptor func tion and/or defective postreceptor events.…”
mentioning
confidence: 99%